Odpowiedzi

2010-03-21T11:42:32+01:00
(3 - x) do kwadratu - (x+1/3) do kwadratu = 2/9
9+x^2-6x - x^2 -1/9 - 2/3x=2/9
-6x-2/3x=2/9-9+1/9
-6 2/3 x = 8 /:(-6 2/3)
x= - 8 : 20/3
x=- 24/20
x=-1 1/5
6 2 6
2010-03-21T11:49:02+01:00
(3-x)² - (x+1/3)²=2/9
9 - 6x + x² - (x² + 2/3x + 1/9) - 2/9 = 0
9 - 6x + x² - x² - 2/3x - 1/9 - 2/9 = 0
-6x - 2/3x = 1/3 - 9
-6⅔x = -8⅔
-20/3x = -26/3 |:(-20/3)
x = 26/20
x = 1 3/10
7 4 7
2010-03-21T11:50:19+01:00
(3-x)²-(x+⅓)²=2/9

ze wzoru skroconego mnozenia:
(3²-2*3*x+x²)-(x²+2*x*⅓+⅓²)=2/9
9-6x+x²-x²+2⅓x+1/9=2/9
9 1/9-4 ⅓x= 2/9
-4 1/3x= -9 1/9+ 2/9
-4 1/3x= -80/9: -13/3
x= 80/39
x= 2i 2/39
3 2 3